A Problem-Based Learning Worksheet: An Effort to Support Students’ Critical Thinking Skills on Cartesian Coordinates Topic - Kinanti, Sekar; Rejeki, Sri (Universitas Wiralodra, 2023)
Critical thinking is one of the essential skills in this 21st century. Students' critical thinking in mathematics has yet to be optimal. Therefore, this study aims to produce Problem-Based Learning Worksheets, particularly on the Cartesian Diagram topic, that are valid and practical to support students' critical thinking skills. The critical thinking skills indicators are giving simple explanations, building basic skills, concluding, giving advanced reasons, and devising strategies. This research uses a 4-D development model consisting of 4 stages: define, design, development, and disseminate. However, this article will only discuss the first three stages. This study involved two experts in mathematics content, two in mathematics learning media, and 34 eight grade public junior high school students in Kartasura, Central Java, Indonesia. The data collection method applied in this study is questionnaires. Based on the data analysis, the worksheet developed is valid (with the good category), with an average score of 4,1 and 4,0 from the content and learning media experts, respectively. At the same time, students' responses on the practicality of the worksheets were an average of 4,2, which is in the excellent category. In addition, it shows that 64,70 % of students reaching the minimum score requirement (75) for the critical thinking test. Therefore, the Problem-Based Learning worksheets developed reach valid and practical categories to support students' critical thinking skills.